Surgical Management of Chest Wall Sarcoma: A Tertiary Cancer Center Experience - Khatiwada, Sagar; Thakur, Binay; Tiwari, Manoj; Bhattarai, Shachee; Kharel, Ashish; Adhikari, Mahesh Mani; Thapa, Shrijana; Sapkota, Sandeep (Nepalese Journal of Cancer, 2025)
Background: Chest wall sarcoma is an uncommon condition, accounting for less than 5% of all thoracic neoplasms. It can arise frombone, cartilage, or soft tissues, depending on its tissue of origin. The most effective treatment approach is surgical resection with adequate margins. Recent research indicates that chemotherapy, whether administered as an adjuvant or neoadjuvant, may improve both overall survival and disease-free survival. This study focuses on examining common histological types, surgical approaches, post-surgical chemotherapy, reconstruction methods, and overall survival outcomes.Methods: Our study included patients who had undergone surgical management for chest wall sarcoma at our center since 2005 to 2020. Data from 39 consecutive patients were collected and entered into the Statistical Package for the Social Sciences (SPSS 16) for analysis.Results: Among 39 patients, the average age was 36 years, with 61% being male. 41% of patient presented delayed with mass size of >10 cm. While 46% underwent surgery alone, 54% received surgery combined with multimodal treatment (radiation and chemotherapy). The median survival was 89 months. Patients with low-grade sarcoma had a significantly better overall survival (Log rank, P